Go slowly, come back quickly - Niven, David (Hamilton, 1981)
They met during the London blitz. Pandora was a small-part actress in a hit musical; Stani, half Polish and half American, found himself alone in England - his father back with his troops in Poland, his mother trapped in France by Hitler's advance.